Experimental Investigation on the Role of Clays in Low Salinity Water Flooding - Wei, Xuemei; Zhang, Yanyu; Jiang, Wenchao; Wang, Zhao; Li, Xiaojun; Wu, Feipeng (Frontiers in Energy Research, 2020)
Clay minerals are regarded as an important factor affecting the results of low salinity water (LSW) flooding. However, most researchers put great attention on their microscopic properties, only few of them investigated the influence of clay minerals by the sand pack flooding experiments. This paper quantifies the effects of clay minerals on LSW flooding with artificial sand pack samples. We used three kinds of sand pack samples (100% quartz sand; 90%/10% quartz sand/kaolinite or montmorillonite) and heavy oil in the LSW flooding experiments. For the samples made of montmorillonite, results show that there exists an optimal salinity range for the LSW flooding. The best salinity range of Na+ is between 1,000 mg/L and 5,000 mg/L, and Ca2+ is between 500 mg/L and 1,000 mg/L. As for kaolinite, a better result will be produced with lower salinity. In addition, using CaCl solution floods samples made of montmorillonite has a better result. A similar phenomenon was also observed when NaCl solution was used to flood kaolinite samples. Respect of flooding modes, the continuous injection of high-low salinity water is more effective, but the LSW flooding method is better considering the economy and time cost.